Pengaruh Kualitas Isi Media terhadap Krisis Kepercayaan pada Generasi Z - Putri, Delviana; Aprianti, Feny (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In recent years, social media has become the largest source of news in digging up information and becoming a place to manage and propose news. Because individuals see it as a trend to switch from traditional media to digital media. Currently, in the era of increasingly advanced and rapid information and communication technology, not only the speed of information dissemination is needed by most people, but also the latest, accurate, and interesting news. This media trust crisis has created a sense of skepticism and distrust of what is conveyed by various media platforms. The beginning of the crisis was due to issues and rumors. The research conducted by the researcher aims to determine the main factors causing Generation Z to lose trust, to find out how the trust crisis can affect Generation Z in consuming news, and what steps are taken to overcome the trust crisis in increasing media literacy to be wiser in consuming news in the media. This study uses a quantitative research method, namely research that uses numbers to conduct research on the process of finding knowledge and using numbers as a tool to research the explanation of what we want to know. So that with this method can provide answers to the research that has been done, using the positivism paradigm. The results of the study revealed that less valid information and clickbait are the biggest contributors to the crisis of trust in Generation Z. On the other hand, media that presents informative content and is based on facts is more appreciated by Generation Z. This study also highlights that Generation Z relies on social media as the main source in meeting their information needs, so that the pattern of news distribution on social media greatly influences their opinions.